The judicial associationism in contemporary democratic societies - Salas Villalobos, Sergio (2007)
This article justify theoretically, the utility of the judicial associationism like one of the components of the doctrine of Democratic Justice. This one, although is developed from the new social molds, includes a series of manifestations that are transformed into rights that the citizens exert so that the State guarantees justice released from any Legal Positivism that was limited and undefined of the expires social justice; that manage in a scene of classes, not always equitable. For that reason, the necessity to justify the judicial associationism,obeys to these new tendencies, transform a social ideology, and fortify it in a Constitutional Governmen